Numerical investigation of water droplet collision dynamics on moving surfaces - Shu Tian; Atena Ghaderi (Scientific Reports, 2025)
Abstract This work presents a comprehensive numerical study on the dynamics of droplet collision on a moving solid surface with different wettabilities. Results of numerical simulations for the cases of both stationary and moving substrates are compared with the corresponding experimental results. The spreading of droplets, lamella formation, and recoil in dependence on droplet size, impact velocity, and motion of the surface are discussed in the present work. The results demonstrate that with large drops and high surface velocities, droplet deformation is strongly asymmetric due to the competition between normal and tangential forces. Also, detachment of the lamella becomes stronger by increasing the speed of the surface; hence, there is only a little recoiling contact with increased energy dissipation. In contrast, the smaller droplets had a quite stable spreading with no lamella breakup at all, which is evidence again for the decisive action of droplet size and kinetic energy in dynamics after impact. Among the other manifestations, the present study points out the formation of a central splash in the larger droplets. These facts increase awareness in droplet dynamics concerning moving surfaces with applications in optimizing the efficiency of industrial processes like inkjet printing, spray cooling, and surface coating technologies.